Optimising the Throughput of a Complex Multimodal Freight Network - Reddy, Denesh (University of the Witwatersrand, Johannesburg, 2025)
This research, situated within the logistic domain, extends its relevance to global supply chains. In a context where revenues are constrained, customer demand for capacity expansion is rising, the commodity mix is evolving, and time sensitivity is critical, relying solely on critical infrastructure expansion for capacity development is neither sustainable nor desirable. Consequently, this study focuses on unlocking latent capacity within existing infrastructure and facilities. Initially, a strategic area for growth was identified, enabling railways to increase their market share in the container sector. The transition of goods from road to rail is a significant economic lever, particularly as the global shift away from fossil fuels continues and railways remain an efficient mode of transport. While bulk commodities are predominantly transported by rail, the Fourth Industrial Revolution presents substantial opportunities in other sectors, notably in the increasing volume of goods suitable for containerization. To address these challenges, a mathematical model was developed to serve as a theoretical foundation for an intermodal hub-and-spoke system, offering a framework for approaching the optimal solution proposed in this thesis. This work makes a novel contribution by addressing the hub network problem with considerations for train lengths and departure decisions. The research investigates whether cost optimisation can be achieved by optimising train lengths. Although the proposed mathematical model is general, it has been specifically applied to a South African context. The optimisation process was carried out using the MATLAB® programming language, and customizing solutions for the specific problem, thereby representing another novel contribution to the field. iv In conjunction, a Simulink® model of a conceptual hub-and-spoke system was developed as a further independent contribution, incorporating key elements to facilitate the study of operations and the impact of varying train lengths. The integration of MATLAB® and Simulink® allowed for solution techniques to be developed using built in optimisation toolboxes, separate from the solution technique developed for the mathematical model. Simulation scenarios were designed to cover a range of operational environments, including considerations for double-stacked container trains. While double stacking is not feasible on narrow-gauge tracks, it provides insight into the potential benefits of transitioning to wider gauges. Results for the South African corridor problem indicate that train lengths can be optimised to achieve lower unit costs, for both the mathematical model and the simulation.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, in the Faculty of Engineering and the Built Environment, School of Mechanical, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Intermodal system; train length; optimisation; genetic algorithm; simulation; mathematical model; SDG-9: Industry, innovation and infrastructure; SDG-8: Decent work and economic growth